Adherence to sepsis protocol in a high-risk maternity reference center - Marianny Medeiros de Moraes; Amuzza Aylla Pereira dos Santos; Juliana Duque da Silva de Sá Leitão; Kassiara Ferreira Felix de Lima Farias; Nathalya Anastácio dos Santos Silva; Núbia Vanessa da Silva Tavares; Kariane Omena Ramos Cavalcante de Melo; Isabel Comassetto (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: To describe the adherence to the sepsis protocol by obstetric nurses in the obstetric triage of a high-risk maternity reference center. Methods: This was a quantitative, documental, and retrospective study involving 105 pregnant women treated in obstetric triage under sepsis criteria. Data were collected through electronic medical records using structured forms and were organized into tables employing descriptive statistics. This research adhered to ethical principles concerning human studies. Results: Of the checklists for initiating the SEPSIS protocol by obstetric nurses, 105 were identified. Regarding the protocol steps performed, lactate was collected in 97.1% of cases and blood cultures in 98.1%, antibiotic therapy was administered in 94.3%, and hydration was carried out in 51.4% of the cases. Conclusion: The initiation of the sepsis protocol for all women meeting the criteria was confirmed. However, the steps were not fully implemented as recommended by the institutional protocol, and the recommended broad-spectrum antibiotic was not administered.